How Relationship Quality Drives Knowledge Sharing on Facebook Brand Pages. Issue 3 (27th May 2023) - Rotchanakitumnuai, Siriluck; Speece, Mark
Abstract: Highly interactive social media brand pages depend on knowledge sharing (KS) within the virtual brand community (VBC). Relationship quality (RQ) is important for fostering KS, but research on how this works in the rapidly evolving context of VBC is still somewhat limited. Much RQ research aggregates RQ components into a reflective second order factor, but disaggregating them allows for better assessment of how RQ works. An online survey among Thai users of Facebook brand pages confirms four components of RQ, including trust in providers and users, conflict, satisfaction, and commitment. Trust positively affects satisfaction and commitment. Conflict reduces satisfaction but does not have a direct impact on commitment, likely because the overall level of conflict was not very high. Satisfaction and commitment both have direct effects on KS, but both trust and conflict are fully mediated by these two RQ sub-dimensions.